Identical or similar brand names used in different countries for medications with different active ingredients: a descriptive analysis. Issue 12 (27th April 2020) - Merchant, Lubna; Lutter, Randall; Chang, Sherry
Abstract : Objective: To identify US drug brand (proprietary) names that are identical or similar to drug brand names used in other countries containing different active ingredients and name confusion medication errors associated with these drugs. Methods: We compared a list of brand names approved by the US Food and Drug Administration from 2006 through 2018 with a list of brand names from other countries generated by Uppsala Monitoring Centre using the WHODrug Dictionary. We evaluated drug name pairs that were identical or highly similar and had different active ingredients and searched for name confusion medication errors with these drugs. Results: A total of 27 US brand names were found to be identical to 38 drug brand names in other countries with different active ingredients. A total of 74 US drug brand names were highly similar to 93 brand names in other countries for drugs containing different active ingredients. We identified name confusion medication errors for one similar name pair. Conclusions: US drug brand names that are identical to or highly similar to brand names in other countries may cause confusion that can lead to medication errors such as wrong drug errors and wrong drug information being consulted. Manufacturers should consider this risk prior to submitting proposed brand names to regulatory authorities. Regulatory authorities may consider incorporating this check in their brand name reviews and work with manufacturers to eliminate the use of the same or similar brand names for products with different ingredients. Consumers filling prescriptions at foreign pharmacies should also be aware of potential name confusion.